SAT0383 High Dose Allopurinol in France, Germany, Italy, Spain and the UK. (23rd January 2014) - Singh, J. A.; Storgard, C.; Baumgartner, S.; Morlock, R.
Abstract : Background: Allopurinol is the most commonly used urate lowering therapy in the world. Although allopurinol is EMEA authorized for up to 900 mg per day, the majority of patients receive 300 mg per day or less. Objectives: To describe physician, patient and treatment characteristics in patients with gout treated with allopurinol. Methods: Data from a quantitative survey of physicians were assessed and results confirmed through chart audits. Initial and current dose of allopurinol, presence of co-morbid conditions, use of prophylaxis for flare prevention, serum uric acid (sUA), physician subspecialty and patient factors were evaluated. Data on achieving target sUA were also collected. Results are presented as proportions or means and standard deviations (SD). Multivariate and descriptive statistics were used to describe patients with sUA ≤ 6 mg/dL. Results: 126 rheumatologists and 126 primary care physicians were interviewed. Of 1260 patients, 816 (65%) were treated with allopurinol. Patient characteristics, treatment and percent with a sUA≤ 6 mg/dL are presented in Table 1 . Across all countries, majority of patients were treated with 300mg or less of allopurinol per day. Less than 6.5% in France, Germany and Spain were given > 300mg whereas 10% in Italy and 34% in the UK achieved a daily dose above 300mg (p<0.01). Over 12 months, the number of patients achieving SUA≤ 6.0 mg/dL differed across the 5 countries (Spain < Germany < Italy < France < UK, Table 1 ), yet, there was no difference in achieving SUA≤ 6.0 mg/dL (average, min or most recent sUA) by allopurinol dose. A multivariable-adjusted model predicting use of high dose allopurinol found patients with tophi (OR 2.49; p=0.01), co-existing alcoholism (OR 2.31; p=0.02), CKD(OR 2.52; p=0.05, patients taking anti-hypertensive(OR 0.28; p=0.03) and from the UK (OR 5.26; p<0.01) were more likely to be using 600mg+ of allopurinol; however, only physician sub-specialty [general practitioners vs. rheumatologists (OR 0.68; p<0.05)], UK vs. other countries (OR 4.01; p<0.01), time on therapy(OR 1.38; p=0.4), and chart documented co-existing CHF (OR 0.4; p<0.05), hyperlipidemia (OR 0.7; p<0.05), hypertension (OR 1.5; p<0.05) and stones (OR 0.4; p<0.05) were associated with sUA ≤ 6 mg/dL. After adjusting for confounding factors there was no impact of allopurinol dose in achieving sUA≤6 mg/dL. Image/graph: Conclusions: Allopurinol is the most widely used urate lowering therapy. Although it is approved for up to 900 mg the majority of patients are treated with 300mg or less per day. Less than 50% of patients achieve sUA<6mg/dL at any dose of allopurinol. Disclosure of Interest: J. Singh Consultant for: URL pharmaceuticals, Savient, Takeda, Ardea, Regeneron, Allergan and Novartis, C. Storgard Employee of: Ardea Biosciences, S. Baumgartner Employee of: Ardea Biosciences, R. Morlock Employee of: Ardea Biosciences